Predictors of Healthcare Utilization Among Older Adults with Moderate to Severe Cognitive Limitations in Ghana: A Cross-Sectional Analysis of the WHO Study on Global Ageing and Adult Health (SAGE) Wave 1 - Dai, Baozhen; Larnyo, Ebenezer; Larnyo, Abigail; Nutakor, Jonathan A.; Amerley Amarteifio, Edwina Naa; Frimpong, Yaw; Addai-Dansoh, Stephen (Current Alzheimer Research, 2022)
Background: As the number of older adults in Ghana keeps increasing, so does the prevalence of aging-related diseases and conditions that tend to lead to cognitive decline. However, knowledge on the predicting factors of healthcare utilization among older adults with cognitive limitations is still scarce. Objective: This study examines the predictive factors of healthcare-seeking behavior among older adults with moderate-to-severe cognitive limitations in Ghana. Methods: Based on Andersen's behavioral model of health service utilization, the study analyzed data from 3106 older adults with moderate to severe cognitive limitations in Ghana aged 50+ using Bivariate Probit Regression and the Heckman Selection Model. Results: Results showed that individuals who were aged 75+, living in urban settlements, educated, higher income levels and parents who had some level of education, pension benefits, and both mandatory and voluntary health insurance were more likely to seek inpatient care. Enabling resources such as the national health insurance scheme and other types of medical insurance, household income, pension benefits, and predisposition factors like education influenced outpatient and inpatient healthcare consumption for older adults with moderate to severe cognitive limitations but had little influence on the choice of healthcare facility except for health insurance. Conclusion: Since the healthcare-seeking behavior of older adults with moderate-to-severe cognitive limitations is driven by an amalgamation of several internal and external factors, there is a need for policy change to understand and cautiously incorporate these factors into the decision to improve equitable access to healthcare services for these individuals, as not all sizes fit all in providing quality care for them.
Keywords: Ghana